Small Lymphocytic Lymphoma Presenting as Breast Mass: A Rare Case Report - Manginstar, Christian; Merung, Marselus A.; Saleh, Denny; Merung, Marcella (e-CliniC, 2024)
Abstract: Primary breast lymphoma is rare and it accounts for around 0.5% of malignant breast neoplasms. Small lymphocytic lymphoma (SLL) is a subtype of non-Hodgkin lymphoma originating from a B-cell lineage. This report presents a case of primary SLL of the breast with lung metastasis that had excellent clinical response. We reported a 67-year-old female complained a right breast mass that suddenly appeared after she got massage on her right left arm. The mass was swollen and painless with no systemic complications. The specimen was submitted to histopathology department and it revealed small diffuse lymphocytic lymphoma. Chest X-ray showed a lung metastasis. The patient was then treated with CHOP regimens (Cyclophosphamid, Doxorubicin, Vincristin, and Prednison) and the clinical result was excellent. The side effects of the medication were minimal. In conclusion, primary breast lymphocytic lymphoma is rare and this case highlights the differential diagnosis for a painless breast mass. The treatment must be individualized and multimodal, with chemotherapy being the most accepted treatment. Keywords: breast lymphoma; breast mass; malignancy